Presentation and outcomes of mitral valve surgery in France in the recent era: a nationwide perspective. Issue 2 (11th August 2020) - Messika-Zeitoun, David; Candolfi, Pascal; Enriquez-Sarano, Maurice; Burwash, Ian G; Chan, Vincent; Philippon, Jean-Francois; Toussaint, Jean-Manuel; Verta, Partrick; Feldman, Ted E; Iung, Bernard; Glineur, David; Obadia, Jean-Francois; et al.
Abstract : Objectives: Unbiased information regarding the surgical management of patients with mitral regurgitation (MR) at the nationwide level are scarce and mainly US-based. The Programme de Médicalisation des Systèmes d'Information, a mandatory national database, offers the unique opportunity to assess the presentation and outcomes of all consecutive mitral valve (MV) surgeries performed in France in the contemporary era. Methods: We collected all MV surgeries performed for MR in France in 2014–2016. MR aetiology was classified as degenerative (DMR), secondary (SMR) or Other (rheumatic or congenital disease and infective endocarditis). Results: During the 3-year period, 18 167 MV surgeries were performed in France (55% repair and 45% replacement; 52% isolated). Age was 66±12 years and 59% were male. Aetiology was DMR in 42%, SMR in 16% and other in 42% including 19% with uncertain aetiologies. Overall, in-hospital mortality was 6.5% and increased with age, female gender, Charlson Comorbidity Index, type of surgery (replacement vs repair), associated surgery (combined vs isolated) and MR aetiology (all p<0.01). In-hospital mortality and rate of death/readmission for heart failure (HF) at 1 year were 3.4% and 13%, respectively for DMR (2.4% and 11% for isolated DMR) and 7.8% and 27%, respectively for SMR (5.5% and 23% for isolated SMR). Repair rate was 55% overall, 68% in DMR and 72% for isolated DMR surgery (70% of all DMR). Repair rates decreased with age, Charlson Comorbidity Index and female sex (all p<0.0001). Conclusion: In this cross-sectional contemporary prospective nationwide database, in-hospital mortality and 1 year rate of death and HF readmission were considerable overall and in all subsets. Repair rates were suboptimal overall especially in the elderly and women subsets. These results underline the need to develop strategies to improve management and outcomes of patients with both DMR and SMR.